Sharia Pension Fund - Muhammad Farid; Mochamad Atim Rudiantoyo Hidayat (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
Pension Fund is a legal entity that manages and runs a program that promises pension benefits. The increasing development of sharias transactions in the financial industry in Indonesia allows pension funds to be managed according to sharia. The purpose of this paper is to determine the basis of fiqh for the development and management of pension funds. Pension Funds are generally regulated in Law no. 11 of 1992. The difference between conventional pension funds and Islamic pension funds is the investment management system carried out to avoid usury and interest-based conventional financial investments.